2014
DOI: 10.1016/j.cub.2014.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Asterless Licenses Daughter Centrioles to Duplicate for the First Time in Drosophila Embryos

Abstract: SummaryCentrioles form centrosomes and cilia, and defects in any of these three organelles are associated with human disease [1]. Centrioles duplicate once per cell cycle, when a mother centriole assembles an adjacent daughter during S phase. Daughter centrioles cannot support the assembly of another daughter until they mature into mothers during the next cell cycle [2–5]. The molecular nature of this daughter-to-mother transition remains mysterious. Pioneering studies in C. elegans identified a set of core pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
123
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(131 citation statements)
references
References 37 publications
(36 reference statements)
6
123
0
Order By: Relevance
“…We visualised them using Asterless (Asl), a component of the Drosophila centriole wall2930 and performed two measurements for each imaging technique: 1) the barrel width (N = 30), and 2) the FWHM of the Asl localisation signal in the centriole wall (N = 60) (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…We visualised them using Asterless (Asl), a component of the Drosophila centriole wall2930 and performed two measurements for each imaging technique: 1) the barrel width (N = 30), and 2) the FWHM of the Asl localisation signal in the centriole wall (N = 60) (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…In these experiments, disengaged centrioles could duplicate during the first interphase of a cycling extract, whereas engaged centrioles required an extra cycle to become disengaged. It has been suggested that recruitment of Asl onto the daughter centriole in Drosophila embryos occurs only once mother and daughter have separated at the end of mitosis and that this provides a duplication license (Novak et al 2014). However, it is notable that in cultured cells, the incorporation of Ana2 and Sas-6 onto the daughter's procentriole once it has disengaged from the mother in telophase appears to mark the very first event in the duplication process (Dzhindzhev et al 2014).…”
Section: The Centrosome and Its Duplication Cyclementioning
confidence: 99%
“…In both Drosophila and mammalian cells, PLK1 then triggers the sequential assembly of CEP135, CEP295/Ana1 and CEP152/Asl and downstream PCM formation 58,89,90 . Importantly, recruitment of Asl in Drosophila embryos only occurs after disengagement, indicating that these licensing processes occur sequentially 93 . In mammalian cells, CEP295 directly binds to CEP192 and contributes to the stabilization of centrioles after the loss of the cartwheel upon mitotic exit 89,94 .…”
Section: Control Of Centriole Numbermentioning
confidence: 99%